The efficacy of digital platforms in the development and relevance of fashion business: Aftermath of COVID-19 - Marfo Ayesu, Solomon; Emmanuel, Amos; Fobiri, George Kwame; Schall, Maud; Boamah, Frederick; Nyarko, Michael Obeng (Papanda Publishier, 2024)
The purpose of the study was to assess how well fashion companies were able to sustain themselves throughout the COVID-19 pandemic by leveraging internet platforms. In spite of the numerous disruptions the fashion industry has experienced as a result of the COVID-19 pandemic's effects on the workplace and the shift in consumer behaviour towards digital platforms, industry stakeholders think that digital platforms offer potential for the industry's revival because many fashion businesses were forced to close during the pandemic. The paper examines and summarises the extent to which digital platforms have been effective in fostering the long-term expansion of fashion companies and their influence on livelihoods in the COVID-19 pandemic, using a narrative literature approach. Based on productive interactions and transactions, digital platforms provide a 21st-century, cost-effective way for businesses to promote themselves. Prior to the pandemic, fashion companies were able to market their goods and services, track live events, keep an eye on trends and projections, and boost their online presence, all of which contributed to increased revenue. Notwithstanding the fact that they continue to face major obstacles that negatively impact the livelihoods of their employees, the study shows how digital platforms have been incredibly effective in helping fashion businesses, especially those in the United States, the United Kingdom, Europe, and Asia, to endure and flourish during COVID-19. Although African customers have become accustomed to online shopping and e-commerce, digital platforms have not been especially popular throughout the continent, as fashion designers and businesses have not properly utilised them. In order to promote fashion businesses and designers, governments and policymakers should support the development of digital infrastructure and digital literacy initiatives. Additionally, fashion brands and businesses in the supply chain should improve their knowledge and understanding of how consumers and potential clients communicate and transact in their online networks. Finally, fashion businesses and designers should invest in social media sentiment analysis tools to facilitate effective online visibility, seamless interactions, and transactions with consumers.